Defensive (Pseudo) Loyalty in Indonesian Textile Manufacturing: A PLS-SEM Study of Job Insecurity and Toxic Workplace Environment - Bella Fujitha; Tasya Aspiranti; Sri Suwarsi (Research Synergy Foundation, 2025)
This study examines how job insecurity and a toxic workplace environment shape employee loyalty in Indonesia's textile manufacturing sector, where cost pressure and employment uncertainty are rising. A quantitative survey was administered to 189 permanent and contract employees using proportional stratified random sampling. Measures captured four dimensions of job insecurity, toxic workplace indicators (ostracism, bullying, and workplace harassment), and three loyalty facets (affective, continuance, and normative). Hypotheses were tested using PLS-SEM with bootstrapping. Job insecurity significantly and positively predicts empliyee loyalty (B = 0.550; t = 4.416; p<0.001). A toxic workplace environment also shows a significant positive effect on loyalty (B = 0.287; t = 2.169; p = 0.030). Together, both predictors jointly explain a substantial portion of loyalty variation (R2 = 0.673), with job insecurity emerging as the stronger driver. These findings suggest that loyalty in this context may reflect defensive or pseudo-loyalty; employees remain and comply not primarily due to emotional attachment, but as an adaptive response to uncertainty, financial dependence, and limited job alternatives. The study contributes by reframing loyalty under stress as multidimensional outcome that can mask hidden disengagement. Practically, organizations should reduce insecurity signals through transparent workforce planning and credible development pathways, while strengthening psychosocial safety systems to mitigate workplace toxicity and convert